2013
DOI: 10.1534/genetics.113.155036
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs of the Ultrabithorax Domain of the Drosophila Bithorax Complex

Abstract: RNA transcripts without obvious coding potential are widespread in many creatures, including the fruit fly, Drosophila melanogaster. Several noncoding RNAs have been identified within the Drosophila bithorax complex. These first appear in blastoderm stage embryos, and their expression patterns indicate that they are transcribed only from active domains of the bithorax complex. It has been suggested that these noncoding RNAs have a role in establishing active domains, perhaps by setting the state of Polycomb Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 49 publications
1
52
0
Order By: Relevance
“…Later, it was suggested that lncRNAs repress Ultrabithorax via transcriptional interference (128). Most recently, genetic inactivation of one such lncRNA resulted in no discernible phenotype (127). Another famous example is pgc , which was first proposed to function as lncRNA (108) but later shown to encode a 71-aa protein responsible for gene function (56).…”
Section: Lncrnas and Transcriptionmentioning
confidence: 99%
“…Later, it was suggested that lncRNAs repress Ultrabithorax via transcriptional interference (128). Most recently, genetic inactivation of one such lncRNA resulted in no discernible phenotype (127). Another famous example is pgc , which was first proposed to function as lncRNA (108) but later shown to encode a 71-aa protein responsible for gene function (56).…”
Section: Lncrnas and Transcriptionmentioning
confidence: 99%
“…The bxd region is transcribed in early embryos and larval/pupal stages to yield polyadenylated transcripts of 1.1–1.3 kb and 0.8 kb. More recently, Bender’s group used embryo in situ hybridizations to provide evidence for 7 additional non-coding transcripts in the Ubx-bxd region, arising from both DNA strands (Pease et al, 2013). …”
Section: A Look At the Past: 30 Years Of Non-coding Transcription Acrmentioning
confidence: 99%
“…For example, although a huge amount of embryonic mRNA-seq and total RNA-seq data now exist, for the most part, these were performed from whole embryo samples. Notably, earlier in situ studies detected transient expression of additional putative short iab RNAs in specific domains of the A/P axis other than A8 and A9 during early embryonic development (Bae et al, 2002; Sanchez-Herrero and Akam, 1989) (Pease et al, 2013), whose molecular identities remain undetermined. One can imagine that further sequencing of polyadenylated and rRNA-depleted RNAs from specific axial domains across development, may produce further insights.…”
Section: A Look At the Past: 30 Years Of Non-coding Transcription Acrmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Pease et al (16) This transcript is expressed in the same domain as Ubx and might be expected to antagonize bxd PRE-bound PcG protein binding and silencing activity. Pease et al found that eliminating transcription through the bxd PRE caused no defect in Ubx expression or any other aspect of fly development (16). So, at least in this case, transcription through the PRE does not appear to be physiologically relevant to antagonize the silencing capacity of this element.…”
mentioning
confidence: 97%